Blended Learning Method for Teaching Reading: The Benefit Impacts for Non-Regular English Class Program - Sari, Puspita; CM Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
Currently e-learning program has been a warm conversation in the world of education so that it can be meaningful way chosen by individuals who want to study, both in regular class and non-regular class. It turns out to greatly affect the learning method used teachers in presenting the material as increasing sophistication of technology. One of the methods used is a blended learning method. This research aims at investigating the benefits of using blended learning in teaching reading class for non-regular English students of the second semester. The method used in this research is descriptive analysis one. In this research students are facilitated by using blended learning method which is essentially a combination of learning excellence that is done face- to- face and virtually. Students should follow 16-week learning process to study Reading for Basic Strategies subject consisting of some activities as follows (1) downloading material every week, (2) taking part in forum discussion virtually (3) completing quiz and assignment, (4) doing mid test and final test, and (5) joining face to face meeting.